Faktor-faktor yang mempengaruhi tahap kesedaran keselamatan dan kesihatan pekerjaan dalam kalangan pelajar kampus sebuah universiti awam - Mohd Hafizul, Mohd Arop (2021)
The study aimed to identify the level of safety and health awareness among USM final year students in Main Campus at three identified school which is, the School of Chemical Sciences, the School of Biology and the School of Industrial Technology. In this study, dependent variables were safety and health awareness and three independent variables were management commitment, safety training and occupational safety and health committee. The research instrument used is a questionnaire involving a total of 207 respondents, namely final year students at the respective schools. The collected data were analyzed using Statistical Package for Social Sciences (SPSS) version 26.0. The analyzes used in this study include Descriptive Analysis, Pearson Correlation Analysis and Multiple Regression Analysis. The results showed that there was a positive relationship between management commitment, safety training and occupational safety and health committee on occupational safety and health awareness among the students. Therefore, a detailed discussion will be described in this study about factors influencing occupational safety and health awareness.